AHR/TET2/NT5E axis downregulation is associated with the risk of systemic lupus erythematosus and its progression - Cheng, He‐Hsiung; Hung‐Ke, Lin; Sheu, Meei‐Ling; Lee, Chun‐Yi; Tsai, Yi‐Ching; Lai, De‐Wei (Immunology, 2023)
The prognosis of systemic lupus erythematosus (SLE) is unpredictable. This study aimed to examine the regulatory mechanism of the AHR/TET2/NT5E pathway during SLE progression. The AHR, TET2 and NT5E expression levels were examined in T regulatory cells (Tregs) of patients with SLE. The correlation of AHR, TET2 or NT5E expression levels with the immunosuppressive functions of Tregs was analysed. In patients with SLE, the number of CD4+IL2RA−FOXP3+ T cell subset was positively correlated with the SLE disease activity index value and negatively correlated with the AHR and TET2 expression levels in CD4+IL2RA+FOXP3+ Tregs. Transcriptional profiles of 79 patients with SLE obtained from the Gene Expression Omnibus database (GSE61635 dataset) revealed a significant positive correlation between the mRNA expression levels of AHR and TET2. In silico analysis predicted that the TET2 promoter comprises an AHR‐binding site. Kynurenine (KYN) promoted the binding of AHR to the TET2 promoter in Tregs of patients with SLE and Jurkat T cell lines. Furthermore, NT5E expression was significantly downregulated in Tregs of patients with SLE, which can be attributed to the dysregulation of NT5E promoter methylation status induced by downregulated TET2 activity. Furthermore, the Treg immunosuppressive activity, which is mediated through the TET2 and A2AR‐adenosine pathways, in the KYN‐treated group was approximately two‐fold higher than that in the control group. The AHR/TET2/NT5E axis mediates the Treg immunosuppressive activity. These findings provide novel insights for the development of therapeutic approaches for SLE and related autoimmune diseases. In summary, this study demonstrated that the downregulated expression of AHR in Tregs resulted in impaired Treg function and development in patients with SLE owing to the dysregulation of the AHR/TET2/NT5E signalling pathway.